Social History of Islamic Banking and First Example: Bank-I Awqāf - Akgunduz, Ahmed (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
The cash waqf was a special category of Islamic endowment and played an important role in the economic/financial history of the Ottoman Empire. As such, it can be considered an important Islamic financial institution that facilitated the flow of funds from those who could save to those who needed capital, i.e. primarily entrepreneurs as well as the general public. This institution is also considered one of the most important Ottoman contributions to Islamic civilisations. Ottoman scholars have been discussing Islamic banking since Suleiman the Magnificent (1574). Islamic banking was known in the Ottoman state as Mu'amalah al-Shar'iyyah, which we can simply call murâbahah. The Ottoman state established the